2020
DOI: 10.3389/fevo.2020.00056
|View full text |Cite
|
Sign up to set email alerts
|

Aphid Facultative Symbionts Aid Recovery of Their Obligate Symbiont and Their Host After Heat Stress

Abstract: Environmental conditions affect insect fitness, with many species constrained by specific temperature ranges. Aphids are limited to temperate climates and it is hypothesized that this is partly due to their heat-susceptible obligate nutritional symbiont Buchnera. Aphids often carry additional facultative symbionts which can increase the host's fitness after heat stress. Here we used the pea aphid (Acyrthosiphon pisum) and three of its facultative endosymbionts (Candidatus Regiella insecticola, Candidatus Fukat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 72 publications
5
58
0
Order By: Relevance
“…Since Hamiltonella reached its highest frequency in 2012 right after a time exceeding the upper critical thermal limit for pea aphid development (Siddiqui et al, 1973), we find it fully plausible that this symbiont confers thermal tolerance under natural conditions. However, some pea aphid studies have found no evidence for thermal tolerance services of Hamiltonella (Heyworth et al, 2020), suggesting a need for further research and that, perhaps, our in-field temperature correlations were driven by baseline Hamiltonella benefits, with costs emerging only under cool temperatures. Accordingly, one Hamiltonella strain related to the Pennsylvania-enriched strain-A was found to drastically reduce the fitness of pea aphid clones under cooler temperatures (18°C) and short day lengths (Simon et al, 2011;Figure S2).…”
Section: Hamiltonella Dynamics? Thermally Regulated Benefitsmentioning
confidence: 83%
“…Since Hamiltonella reached its highest frequency in 2012 right after a time exceeding the upper critical thermal limit for pea aphid development (Siddiqui et al, 1973), we find it fully plausible that this symbiont confers thermal tolerance under natural conditions. However, some pea aphid studies have found no evidence for thermal tolerance services of Hamiltonella (Heyworth et al, 2020), suggesting a need for further research and that, perhaps, our in-field temperature correlations were driven by baseline Hamiltonella benefits, with costs emerging only under cool temperatures. Accordingly, one Hamiltonella strain related to the Pennsylvania-enriched strain-A was found to drastically reduce the fitness of pea aphid clones under cooler temperatures (18°C) and short day lengths (Simon et al, 2011;Figure S2).…”
Section: Hamiltonella Dynamics? Thermally Regulated Benefitsmentioning
confidence: 83%
“…Additionally, variations in the strength of protection against the fungal pathogen P. neoaphidis have also been observed among different endosymbiont strains of R. insecticola studied in two S. avenae clones [ 56 ]. Other endosymbiont-related functions have been recently suggested for heat stress by R. insecticola in the pea aphid [ 71 ], but such a protective effect differs from previous studies [ 59 , 72 ], suggesting that effects mediated by facultative endosymbionts can be dependent on symbiont and host genotypes or their interaction [ 71 ].…”
Section: Discussionmentioning
confidence: 92%
“…However, this reduction is significantly less in aphids that are infected with either of the two facultative symbionts Regiella insecticola or Fukatsuia symbiotica. Moreover, it was observed that the reduced population density of the obligate symbiont, Buchnera, as a result of heat shock, could be successfully recovered in aphids infected with Regiella or Fukatsuia, but not in uninfected insects (Heyworth et al, 2020). Thus implying that sensitivity of Buchnera to heat shock, as a consequence of extreme gene loss, is compensated by the co-residing facultative symbionts.…”
Section: Implications Of Genome Size Reduction For the Endosymbiotic mentioning
confidence: 99%